"Tax" and "Fee" Message Frames as Inhibitors of Plastic Bag Usage Among Shoppers: A Social Marketing Application of the Theory of Planned Behavior. (September 2016) - Muralidharan, Sidharth; Sheehan, Kim
In response to the plastic bag pandemic, many studies have indicated that penalties can lower consumption of plastic bags but are only effective in the short term. For long-term impact, shoppers' intrinsic motivations need to be explored. Using framing and the theory of planned behavior, the current study looked at how advertising messages framed as "avoiding a fee" (gain) and "paying a tax" (loss) can impact shoppers' behavior to bring reusable bags. Findings from a hierarchical and multiple regression analysis showed differences in how both frames were interpreted. For the fee frame, attitude toward compliance and perceived control were important to intentions, while attitudes toward bringing reusable bags, control, and subjective norms impacted intentions for the tax frame. Behavioral intention was the main predictor of behavior for both frames. The findings suggest that a penalty framed as a tax maybe more effective in motivating shoppers to bring reusable bags. Theoretical and practical implications are discussed.